ANALISIS PEMANFAATAN DAN PENGEMBANGAN HUTAN WISATA TAWANGMANGU - Falah, Darul (Jurnal Wana Tropika, 2019)
Tawangmangu Ecotourism Forest located at Karanganyar District, have potency of natural view and unique landscape as natural ecotourism and education. Characteristics of visitor and its demand, tourism area wide (Douglas, 1982), maximum area for tourism (Soemarwoto, 1985), and physical building wide (Pamulardi, 1994) area very useful to analysis of benefit and its developmentResearch is conducted by questionnaire with accidental sampling method for visitor, field measurement for plysical building and gathering of secondary data from tourism office. The result indicate that total physical building and its facilities is 6.5% and area of tourism is 15% from total ecotourism forest area. Main visitors are high school students, college students, and domestic tourist with age 15 – 30 years old. They came from Karanganyar, Sragen, Semarang and Yogyakarta. By SWOT analysis, strategy of development of Tawangmangu ecotourism forest can be done by some following steps : rearrangement distribution of visitor not only around water fall, but also another interested object, differentiations of holiday ticket and non holiday ticket in order to visitors at holiday not overland, development some new object around waterfall in order to visitor not accumulated around waterfall, make new alternative tourism packages which interesting and variety, approach of indigenous culture and art for some object, and development of new marketing strategy for national scale. Keywords: Benefit Analysis, Ecotourism Forest